Impact of Scanbody Geometry and CAD Software on Determining 3D Implant Position - Kropfeld, Judith; Berger, Lara; Adler, Werner; Schulz, Katja; Motel, Constantin; Wichmann, Manfred; Matta, Ragai (Dentistry Journal, 2024)
The implementation of CAD software in the digital production of implant prosthetics stands as a pivotal aspect of clinical dentistry, necessitating high precision in the alignment of implant scanbodies. This study investigates the influence of scanbody geometry and the method of superimposing in CAD software when determining 3D implant position. A standardized titanium model with three bone-level implants was digitized to create reference STL files, and 10 intraoral scans were performed on Medentika and NT-Trading scanbodies. To determine implant position, the generated STL files were imported into the Exocad CAD software and superimposed—automatically and manually—with the scanbody geometries stored within the software’s shape library. Position accuracy was determined by a comparison of the 3D-defined scanbody points from the STL matching files with those from the reference STL files. The R statistical software was used for the evaluation of the data. In addition, mixed linear models and a significance level of 0.05 were applied to calculate the p-values. The manual overlay method was significantly more accurate than the automatic overlays for both scanbody types. The Medentika scanbodies showed slightly superior precision compared to the NT-Trading scanbodies. Both scanbody geometry and the type of alignment in the CAD software significantly affect digital workflow accuracy. Manual verification and adjustment of the automatic alignment process are essential for precise implant positioning.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Computer-Aided Design/Computer-Aided Manufacturing (CAD/CAM); digital workflow accuracy; implant dentistry; intraoral scanning (IOS); scanbody geometry